Voice Behavior: The Role of Perceived Support and Psychological Ownership - Andiyasari, Andin; Matindas, Rudolf W.; Riantoputra, Corrina D. (The South East Asian Journal of Management, 2017)
This study aims to delineate the key socio-emotional needs important for voice behavior. To do this, we examine individual and contextual factors as mechanisms underlying how psychological ownership and perceived support influence employee voice behavior. Employing survey research of 210 employees from two big companies in Indonesia, analyses revealed that perceived supervisor support had direct and indirect effects on voice behavior, and job-based psychological ownership is a crucial mediator of the relationship between organization-based psychological ownership and perceived supervisor support on voice behavior. Path analysis offered further support for the complete model (χ2= 4.25, df = 3, P-value = 0.235, RMSEA = 0.045). The present study contributes to current understanding by demonstrating that psychological ownership (i.e., an individual characteristic) and perceived supervisor support (i.e., a contextual characteristic) dynamically affect voice behavior. We discuss implications for research on voice behavior by highlighting key drivers to support employees’ emotional needs that are essential for voice behavior.